2022
DOI: 10.3390/ijms231810329
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanoplastics’ Effects on Protein Folding and Amyloidosis

Abstract: A significant portion of the world’s plastic is not properly disposed of and, through various processes, is degraded into microscopic particles termed micro- and nanoplastics. Marine and terrestrial faunae, including humans, inevitably get in contact and may inhale and ingest these microscopic plastics which can deposit throughout the body, potentially altering cellular and molecular functions in the nervous and other systems. For instance, at the cellular level, studies in animal models have shown that plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 114 publications
0
18
0
Order By: Relevance
“…Other modern issues pertain to our exposure to pollution and its detrimental effects on our health. For instance, micro- and nano-plastics have entered the food chain, and evidence suggests they can enter cells and alter the native state of physiological proteins, potentially playing a role in the pathogenesis of amyloids too [ 116 ]. Clearly, today’s challenges are different from those of a few decades ago, and they should be taken into consideration for the timely progress in the field of innovative insulin therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Other modern issues pertain to our exposure to pollution and its detrimental effects on our health. For instance, micro- and nano-plastics have entered the food chain, and evidence suggests they can enter cells and alter the native state of physiological proteins, potentially playing a role in the pathogenesis of amyloids too [ 116 ]. Clearly, today’s challenges are different from those of a few decades ago, and they should be taken into consideration for the timely progress in the field of innovative insulin therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A study using molecular dynamic simulations showed that 5 nm polyethylene nanoplastics increased the presence of protein α-helices, while nylon nanoplastics induced the unfolding of helical structures and promoted the formation of β-sheet structures [ 46 ]. This suggests that nanoplastics may interact with secondary protein structures and is postulated to be a potential cause of amyloidosis, a key process implicated in diseases such as Parkinson’s disease and Alzheimer’s disease [ 47 ].…”
Section: Proposed Mechanisms Of Tissue and Cell Damagementioning
confidence: 99%
“…31,75 M/NPs in the aquatic environment can easily interact with the bio-molecules such as nucleic acid and proteins secreted by the aquatic organisms. 76,77 The particle surface will undergo substantial changes owing to these interactions and this alters the biological reactivity of the particles altogether. 78,79 Sometimes, the particles can be internalized by the organisms, and they can interact with the biomolecules in the intracellular environment leading to formation of BC.…”
Section: Biocorona Formation On M/npsmentioning
confidence: 99%